A new species of Pandanus-dwelling frog from northern Madagascar related to Guibemantis pulcher - Vences, Miguel; Hutter, Carl R.; Glaw, Frank; Rakotoarison, Andolalao; Raselimanana, Achille P.; Scherz, Mark D. (Zootaxa, 2023)
Populations of phytotelmic frogs from northern Madagascar assigned to Guibemantis (Pandanusicola) pulcher are known to differ genetically from populations further south in the eastern rainforest belt of the island, but to date, their status has not been analyzed in depth. We combined molecular genetic data with an examination of color pattern to clarify the taxonomy of these frogs. DNA sequences of both mitochondrial and nuclear-encoded genes were consistently differentiated between the northern populations and those occurring further south. Uncorrected pairwise distance in the 16S rRNA gene was 3.7‒4.3% and thus at a level usually characterizing distinct frog species in Madagascar. Furthermore, the northern specimens were characterized by more and smaller purplish-brown spots on their green dorsal surface, and a less distinct brown patch on the flanks. Although fully conclusive evidence for the species status of the northern lineage from bioacoustic differences, sympatric occurrence or narrow hybrid zone is currently lacking, such species-level distinctness is currently the most likely hypothesis. We therefore name the northern populations as Guibemantis (Pandanusicola) pulcherrimus sp. nov. The new species is known from Makira (type locality) and Bemanevika, and specimens morphologically assignable to this taxon have also been recorded from Masoala, Marojejy and Anjanaharibe-Sud.